Analysis of Human Capital Development and Output Growth Nexus in Africa's Most Populous Country: A New Evidence from ARDL Approach. (December 2020) - Orji, Anthony; Ogbuabor, Jonathan E.; Iwuagwu, Chikaodinaka; Anthony-Orji, Onyinye I.
This article empirically analysed the impact of human capital development on output growth in Nigeria, Africa's most populous country. The study employed time series data from 1985 to 2018 and adopted the autoregressive distributed lag (ARDL) model bounds test to ascertain the existence of a long-run relationship between human capital development and output growth. The findings of this study revealed that there exists a long-run relationship between human capital development and output growth in Nigeria. Human capital development components such as public expenditure on health and labour force showed significant positive contribution to output growth in Nigeria, while public expenditure on education showed a reverse relationship. Gross capital formation (proxy for stock of physical capital) also showed positive contribution to growth. The study therefore recommended that there is need to re-evaluate the expenditure made on public education to ensure that it is well utilised to fund critical infrastructure that will enhance learning, capacity building and human development, which will ultimately contribute to output growth. Policies should also be enacted to support improvements in the other components of human developments' proxies in order to contribute optimally to output growth continuously.